Searching for Social Justice: Hunger, Malnutrition and Food Insecurity of Rohingya Refugees (International Journal of Food and Nutritional Sciences, 2022)
This article examines how various vulnerabilities/issues faced by Rohingya refugees living in Cox's Bazar, Bangladesh, and other camps across world have been exacerbated before, during and after the COVID-19 pandemic. Both direct and indirect repercussions of COVID-19 mitigation strategies have served to heighten pre-existing risks, preventing children and adolescents from reaching their full capabilities. This study aimed to examine the prevalence of various issues like hunger, food insecurity, Unhygienic Food, Mal-nutrition etc faced by Rohingya refugees at different refugee camps.